Iron-catalysed highly selective hydroalkoxycarbonylation of alkynes using CO as C1 source - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (Catalysis Science & Technology, 2023)
Though precious and rare, late-transition metals have been extensively used in metal-catalysed carbonylation reactions in organic transformations. On the other hand, base metals are abundant and cheap, but their practical utilization in carbonylation reactions is rarely explored. Here, we report iron-catalysed hydroalkoxycarbonylation of alkynes to alpha,beta-unsaturated esters in one pot. A readily available iron precursor [Fe2(CO)9] in the presence of a diimine ligand L7 catalyzes the conversion of alkynes to alpha,beta-unsaturated esters under 10 bar CO pressure. This operationally simple protocol tolerates various functional groups and allows facile access to about 40 alpha,beta-unsaturated esters. The synthetic utility of the reaction has been demonstrated by scaling up the reaction to 1 g and by preparing sunscreen/antifungal agents. The kinetic study suggests that the reaction is an approximate 1st order with respect to the iron catalyst, and the initial rate of the reaction is 3.6 x 10-2 M h-1. Mechanistic investigations using NMR spectroscopy indicated the existence of an [Fe-H] intermediate, and control experiments using a radical trapping reagent and EPR revealed the absence of any radical species in the reaction. Precious and rare, late transition metals have been extensively used in carbonylation. An earth abundant iron-catalyst is reported here for hydroalkoxycarbonylation of alkynes in the presence of CO as C1 source.

Iron-catalyzed alkoxylation, dehydrogenative-polymerization and tandem hydrosilylative-alkoxylation - Sen, Anirban; Kumar, Rohit; Tewari, Tanuja; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry- a european journal, 2023)
Alkoxylation, hydrosilylative-alkoxylation, and dehydrogenative-polymerization are some of the most widely used transformations in synthetic chemistry. However, these transformations are traditionally catalyzed by precious, and rare late-transition metals. Presented here is a molecularly defined iron complex that catalyzes alkoxylation, tandem hydrosilylative-alkoxylation, and dehydrogenative polymerization of silanes under mild conditions. The iron complex [Fe(CO)(4)(H)(SiPh3)] 1 catalyzes a direct Si-O coupling reaction between an array of silanes and alcohols to produce desired alkoxysilanes in excellent yield, with H-2 as the only byproduct. The iron catalyst tolerates various functional groups and provides access to 20 alkoxysilanes, including essential molecules such as & beta;-citronellol and cholesterol. Further, complex 1 catalyzes the polymerization of renewable diol and silane monomer to produce a renewable and degradable poly(isosorbide-silyl ether). Remarkably, complex 1 catalyzes a tandem hydrosilylative-alkoxylation of alkynes under mild conditions to yield unsaturated silyl ethers. The synthetic utility has been demonstrated by gram-scale alkoxylation and hydrosilylative-alkoxylation reactions.
Keywords: alkoxylation; dehydrogenative polymerization; earth abundant catalysts; hydrosilylative-alkoxylation; Iron Catalyst

Iron-catalyzed magnesium-mediated formal hydroformylation of alkynes and alkenes - Tewari, Tanuja; Kumar, Rohit; Chikkali, Samir H. (ChemCatChem, 2023)
Alkynes and alkenes are routinely converted to corresponding synthetically versatile aldehydes using rhodium-catalyzed hydroformylation. However, rhodium is rare, precious, costly, and depleting at a considerably high rate. Reported here is iron-catalyzed, magnesium-mediated, formal hydroformylation of alkynes and alkenes in the absence of syngas. Readily available FeCl2 in the presence of alkyl magnesium halide, and dimethyl formamide, catalyzes hydroformylation of various alkynes and selectively produces alpha,beta-unsaturated aldehydes in good to excellent conversion. Mechanistic investigations revealed the presence of vinyl magnesium intermediate, the kinetic study disclosed the first-order dependence of the reaction on iron loading, and the control experiment authenticated the iron catalyst's homogeneous nature. The scope of this methodology was amplified, and 20 alkenes were examined. [Fe(acac)(3)] in the presence of ligand, alkyl magnesium halide, and dimethyl formamide catalyzed the hydroformylation of alkenes and displayed good to excellent conversion. An earth-abundant iron catalyst offering a syngas cylinder-free safe alternative to high-pressure hydroformylation has been reported.
Keywords: aldehydes; alkenes; Alkynes; Hydroformylation; iron catalysis

Iron in organometallic transformations: a sustainable substitute for noble metals - Kumar, Rohit; Tewari, Tanuja; Chikkali, Samir H. (ChemCatChem, 2024)
Transition metal catalysis plays a pivotal role in chemical synthesis. Noble metals often grab significant attention in organometallic catalysis due to their high reactivity. However, the serious issues associated with these metals such as low abundance, toxicity, geopolitical limitations, and volatile prices are driving the scientific community to discover sustainable alternatives. In this context, iron appears to be the first choice as an alternative metal due to its unique properties, including a range of stable oxidation states, Lewis acidity, high abundance in the earth's crust, and low toxicity. Over the past two decades, substantial progress has been made in iron catalysis. This overview examines the recent developments in iron-catalyzed industrially relevant transformations such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. As witnessed throughout this review, the performance of iron can be significantly altered by suitable ligand selection and by tailoring the electronic and steric properties of the iron center. While noble metals remain the industry work-horse, iron is inching closer and with extensive scientific understanding, it may replace noble metals in the near future. Late transition metals catalyze several reactions and have been the industry work-horse for decades. While, earth abundant metals are rarely used in industrially relevant transformations. In this overview, we examine the recent development in iron-catalyzed industrially relevant reactions such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. Iron is inching closer and may replace noble metals in near future. image
Keywords: Alkene Isomerization; alkyne; Carbonylation; depolymerization; Hydrophosphination; Hydrosilylation; iron catalysis

Iron-catalyzed (E)-selective hydrosilylation of alkynes: scope and mechanistic insights - Sen, Anirban; Tewari, Tanuja; Kumar, Rohit; Vinod, C. P.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Catalysis Science and Technology, 2024)
Iron-catalyzed hydrosilylation of internal alkynes has been rarely reported. Even in these rare cases, additives have been used for the success of the reaction, which often creates a problem for the functional group tolerance of the reaction. Herein, we report an additive-free iron-catalyzed (E)-selective hydrosilylation of internal alkynes in the presence of a phosphine ligand. A low-valent Fe(0) complex [Fe(CO)(3)(BDA)] {[Fe-1]} catalyzed the hydrosilylation of alkynes at 60 to 120 degrees C, exhibited a broad substrate (24 substrates) scope and tolerated different functional groups. The synthetic utility of the reaction was demonstrated by a gram scale experiment, preparing alkenes, and by chemo-selective hydrosilylation. The modus operandi of the reaction has been investigated by i) homogeneity test, ii) radical trapping experiments, iii) X-ray photoelectron spectroscopy, and iv) by preparing a Fe(II) complex as catalyst control. These mechanistic investigations revealed a two-electron pathway for the hydrosilylation of alkynes. In addition, kinetic investigations were undertaken to shed light on the rates of the reaction. Kinetic studies suggest the absence of an induction period, and the reaction is first order with respect to the concentration of iron catalyst [Fe-1] and zeroth order with respect to the substrate (alkyne). The Hammett plot suggests that strongly electron-withdrawing groups on the alkyne favour the hydrosilylation reaction. Meanwhile Eyring analysis suggests that the rate-determining step likely involves an associative pathway. Based on the findings of the mechanistic and kinetic investigation, a plausible Chalk-Harrod-type mechanism is likely to be operative. The proposed mechanism is substantiated by computational investigations, which suggested that the Chalk-Harrod mechanism is kinetically more favored by 15.8 kcal mol(-1) over the modified Chalk-Harrod mechanism.

Integrated flue gas CO2 capture and conversion to formate: a sustainable approach - Kumar, Rohit; Majumder, Supriyo; Singh, Chadrodai Pratap; Samanta, Chanchal; Newalkar, Bharat L.; Krishnamurty, Sailaja; Das, Raj Kumar (ChemSusChem, 2025)
Industrial CO2 emissions, characterized by dilute streams and impurity complexity, demand energy-efficient mitigation strategies beyond conventional capture technologies. Here, an integrated CO2 capture and conversion (ICCC) system is reported employing a heterogenized iridium catalyst-hydroxyquinoline-ligated Cp*Ir-Cl immobilized on amine-functionalized silica-that directly converts CO2 from synthetic flue gas containing SOx, NOx, and O2 to formate with 100% selectivity. The catalyst delivers remarkable activity, achieving turnover numbers up to 10,286 within 16 h. Density functional theory reveals that its square pyramidal geometry, induced by the hydroxyquinoline ligand, enhances Ir-N(ring) bond strength and electronic delocalization, thereby improving hydration energy, structural robustness, and catalytic efficiency. Importantly, the catalyst system demonstrates excellent durability, maintaining full activity over five regeneration cycles. Hydrogenation in a 1 M DABCO medium, followed by thermal decomposition of the amine-formate adduct at 150 degrees C, enables efficient lean amine regeneration, allowing subsequent flue gas capture and formate production without performance loss. This closed-loop strategy delivers a sustainable, contaminant-tolerant, and recyclable CO2-to-formate platform with strong promise for scalable industrial deployment.
Keywords: CO2 capture; flue gases; integrated capture and conversions; net zero future; Recycle